2011
DOI: 10.1007/s10689-010-9414-x
|View full text |Cite
|
Sign up to set email alerts
|

German national case collection for familial pancreatic cancer (FaPaCa): ten years experience

Abstract: Familial pancreatic cancer (FPC) is a rare hereditary tumor syndrome. The 10-years experience of the national case collection for familial pancreatic cancer of Germany (FaPaCa) is reported. Since 1999 FaPaCa has collected families with at least two first-degree relatives with confirmed pancreatic cancer (PC), who did not fulfill the criteria of other hereditary tumor syndromes. Histopathological verification of tumor diagnoses, and genetic counseling were prerequisites for enrollment of families in FaPaCa. 94 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 38 publications
3
137
0
3
Order By: Relevance
“…During long term follow-up [36] (24 mo-extended surveillance), this study showed histologically proven precancerous or cancerous lesions in 4 individuals (5.5%) and additional branch duct IPMN in 5 ones, with a diagnostic yield of up to 12.5%, close to the previous rates reported by the Johns Hopkins and the Rotterdam groups.…”
Section: Screeningsupporting
confidence: 84%
See 3 more Smart Citations
“…During long term follow-up [36] (24 mo-extended surveillance), this study showed histologically proven precancerous or cancerous lesions in 4 individuals (5.5%) and additional branch duct IPMN in 5 ones, with a diagnostic yield of up to 12.5%, close to the previous rates reported by the Johns Hopkins and the Rotterdam groups.…”
Section: Screeningsupporting
confidence: 84%
“…This risk has been estimated to be 2.3 to 4.5-fold greater in individuals with one FDR with pancreatic cancer, 6.4-fold greater in individuals with two FDRs with the disease and 32 to 57-fold greater in individuals with three or more FDRs affected [29][30][31][32] . Similarly to other familial tumors, the median age of presentation in patients with FPC is up to 20 years earlier than in patients with sporadic cancer (49 years vs 61 years) [33][34][35] with an ''anticipation phenomenon'' in the affected kindred and a trend to become more severe and appear at an earlier age as the disorder is passed from one generation to the next [35,36] . Currently, the genetic etiology of most cases of FPC remains undetermined but complex segregation analysis of these patients has led to the discovery of various candidate pancreatic cancer susceptibility genes such as BRCA2 (6%-17% of cases) [37,38] , partner and localizer of BRCA2 (PALB2) (1%-4% of cases) [39,40] and palladin, even if mutations of the latter have been identified in normal controls as well [41][42][43] .…”
Section: Familial Pancreatic Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…EUS-FNA is the preferable approach in resectable disease because of better diagnostic yield and lower risk of peritoneal seeding compared to percutaneous approach [49,50].…”
Section: Summary Of National Comprehensive Cancer Network (Nccn) Guidmentioning
confidence: 99%